Working Women in the Sandwich Generation: Theories, Tools and Recommendations for Supporting Women's Working Lives 2022
DOI: 10.1108/978-1-80262-501-120221002
|View full text |Cite
|
Sign up to set email alerts
|

How Do They Manage? Coping Strategies of the Working Sandwich Generation in Flanders

Abstract: Drawing on in-depth interviews with 34 women and men of the working sandwich generation (WSG) in Flanders, this chapter presents a taxonomy of nine coping strategies that the WSG uses to balance intergenerational care with a job: an acceptance strategy, a boundary management strategy, a help-seeking strategy, a planning strategy, a governance strategy, a self-care strategy, a time focus strategy, a values strategy and a super-sandwich strategy. Individuals of the WSG do not use just one strategy, but combine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Receiving social assistance, prioritizing oneself, allocating time for mental and physical strategies, and engaging in social relationships are among the solutions that were shared between the results of this study and other studies. But solutions such as the desire to be temporarily away from the family to reduce the pressure of care, the desire to live independently from the elderly, and mediation by previous studies, have not been confirmed or rejected [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Receiving social assistance, prioritizing oneself, allocating time for mental and physical strategies, and engaging in social relationships are among the solutions that were shared between the results of this study and other studies. But solutions such as the desire to be temporarily away from the family to reduce the pressure of care, the desire to live independently from the elderly, and mediation by previous studies, have not been confirmed or rejected [23,24].…”
Section: Discussionmentioning
confidence: 99%